Rahasia Di Balik Kesuksesan: Strategi Cerdas UMKM Kuliner Dalam Mengelola Risiko - Pangestuti, Dewi; Senny, Nila; Aurel, Princes; Anayya, Miska; Varga, Fatimah; Putri, Dina Rachma; Nafilaty, Najwa Laila (PT WIM Solusi Prima, 2024)
The objective of this community service activity is to evaluate the risk management practices employed by Cahaya Sop Ikan MSME in order to ascertain the efficacy of the strategies utilized to address the inherent risks associated with this culinary enterprise. A qualitative approach is employed in this analysis to identify and assess the various risks faced by the business, including those related to inventory, competition, pricing, reputation, food safety and quality, and financial risk. The results of this abdimas activity demonstrate that, despite the considerable challenges faced by MSMEs, business owners are capable of effectively mitigating these risks through the implementation of strategic measures, including competitive pricing and quality assurance. A comprehensive assessment reveals that a thorough comprehension of risk is pivotal for effective risk management and risk mitigation strategies. Furthermore, this service activity offers invaluable insights into how MSMEs can enhance their operations through risk analysis and feedback from interviews with business owners. One of the pivotal recommendations is the utilization of social media to expand market reach and enhance business reputation. Other suggestions include conducting regular risk analysis, improving branding, and building robust relationships with trusted partners or suppliers. Kegiatan pengabdian pada masyarakat ini bertujuan untuk mengevaluasi manajemen risiko pada UMKM Cahaya Sop Ikan untuk menilai keefektivitasan penanganan risiko yang dihadapi oleh usaha kuliner ini. Dengan pendekatan kualitatif, analisis ini mengidentifikasi dan menilai berbagai risiko yang dihadapi, seperti risiko persediaan bahan masakan, persaingan, harga, reputasi, kesehatan dan kualitas makanan, serta risiko keuangan. Hasil kegiatan abdimas ini menunjukkan bahwa meskipun UMKM menghadapi tantangan signifikan, pemilik usaha mampu mengatasi risiko-risiko tersebut dengan strategi yang efektif, termasuk pemberian harga dan kualitas yang kompetitif. Evaluasi mendalam menunjukkan bahwa pemahaman terhadap risiko adalah kunci untuk pengelolaan yang baik dan mitigasi risiko yang efektif. Selain itu kegiatan pengabdian ini juga memberikan wawasan berharga tentang bagaimana UMKM dapat meningkatkan operasionalnya melalui analisis risiko dan masukan dari wawancara dengan pelaku usaha. Salah satu rekomendasi utama adalah pemanfaatan media sosial untuk memperluas jangkauan pasar dan meningkatkan reputasi usaha. Saran lain termasuk melakukan analisis risiko secara rutin, meningkatkan branding, dan membangun hubungan yang kuat dengan mitra atau supplier terpercaya.